Enhanced electro-Fenton processes by persulfate radical for atenolol oxidation from aqueous solution - Maryam Chatraee; Afshin Ebrahimi; Ali Fatehizadeh (Environmental Health Engineering and Management, 2022)
Background: Pharmaceuticals and personal care products (PPCPs) are a group of emerging environmental pollutants that have attracted the attention of many researchers due to their harmful effects on aquatic environment, animals, and humans. Thus, it is necessary to remove these contaminants from water resources. This study aimed to assess the efficiency of enhanced electro-Fenton (EF) process by persulfate (PS) radical for removal of atenolol (ATL) from aqueous solutions. Methods: The bench scale experimental setup was used to examine the factors affecting the ATL removal efficiency from synthetic wastewater; supporting electrolyte type, pH, contact time, PS concentration, Fe concentration, and ATL initial concentration. Results: Based on the results, ATL removal efficiency of 78.6% was reached under the optimum conditions of enhanced EF process by PS radical. The optimum conditions included NaCl (as a supporting electrolyte) dose of 0.5 g/L, pH 5, contact time of 60 minutes, PS dose of 0.15 g/L, Fe dose of 0.15 g/L, current density (CD) of 1.5 A/m2, and ATL concentration of 40 mg/L. Kinetic model was following the second-order kinetics. Conclusion: The studied advanced oxidation process (AOP) can effectively remove ATL from aqueous solutions. Therefore, it can be used as an effective technique for removing other organic matter from the wastewater.